Kerohanian Sejagat: Satu Perspektif terhadap Ajaran Universal Sufism - Nozira Salleh; Faudzinaim bin Hj. Badaruddin; Dato' Zakaria Stapa (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Universal spiritual teachings are still neglected by most Islamic scholars due to the  thought that the teachings do not have a great influence to Muslims. But in reality, these  teachings won the hearts of Muslims in many Islamic countries such as Indonesia, Turkey,  Pakistan and others. Therefore, this article attempts to describe this fact by focusing the  discussion on the teachings of Universal Sufism, as one of the universal spiritual teachings that  are increasingly getting attention of Muslims in particular and mankind in general. The  description also involves the assessments based on the Quran as the main guide of Muslims,  which is expected to establish a clear understanding of Muslims about the spiritual teachings  that are justified and not justified by the Islamic Shari'a.